Neuropsychological performance of Finnish and Egyptian children with autism spectrum disorder. Issue 1 (31st January 2016) - Elsheikh, Sherin; Kuusikko-Gauffin, Sanna; Mattila, Marja-Leena; Jussila, Katja; Ebeling, Hanna; Loukusa, Soile; Omar, Manal; Riad, Geylan; Rautio, Arja; Moilanen, Irma
Abstract : Background: Previous studies investigating neuropsychological functioning of children with autism spectrum disorder (ASD) have only analysed certain abilities, such as executive functions or language. While comprehensive assessment of the neuropsychological profile of children with ASD has been the focus of recent research, most of the published evidence originates from single centres. Though studies on differences in neuropsychological features of children with ASD across countries are essential for identifying different phenotypes of ASD, such studies have not been conducted. Objective: Our goal was to assess the neuropsychological abilities of children with ASD in northern Finland and Egypt and to examine the effect of age and intelligence quotient (IQ) on these abilities. Design: Selected verbal and non-verbal subtests of the neuropsychological assessment NEPSY were used to examine 88 children with ASD in northern Finland (n=54, age M=11.2, IQ M=117.1) and Egypt (n=34, age M=8.4, IQ M=96.6). Results: Finnish ASD children scored significantly higher than their Egyptian counterparts on the verbal NEPSY subtests Comprehension of Instructions (p<0.001), Comprehension of Sentence Structure (p<0.01), Narrative Memory (p<0.001) and Verbal Fluency (p<0.05) and on the non-verbal NEPSY subtest Design Fluency (p<0.01). Finnish and Egyptian ASD children did not differ on the subtests Memory for Faces, Object Recognition and Object Memory. In addition, we found that age and verbal IQ can have significant influence on neuropsychological performance. Conclusions: Our results suggest a possible cultural impact on verbal and visuomotor fluency. However, the ability to recognize and memorize objects and the disability to remember faces appear to be typical for ASD and culturally independent.